University as a publisher – how to create an efficient and low-threshold scholarly publishing process - Mure, Laura (Septentrio Conference Series, 2017)
Aalto University established its own publication series in 2011 and the current annual publication volume is almost 300 items. Most of the publications are doctoral dissertations. The integral part of the publication activities is the web service called publication platform The proposed poster would discuss how the publication platform functions from the view-point of an author, how it integrates into other existing systems, such as the institutional repository, and to the services of the university printing house. As such, it provides a case example on how to create an efficient and low-threshold scholarly publishing process, which integrates university’s own publications into diverse publication repositories and research information systems used by universities today.